LEGAL RESPONSIBILITY FOR PERPETRATORS OF TAX CRIMES BASED ON THE CORRUPTION CRIMINAL ACTS LAW - Rahmayanti; Chairuni Nasution; alfriz hutabarat (Yayasan Multidimensi Kreatif, 2025)
Eradication corruption is one of priority main in effort create clean and accountable government . Enforcement law in case taxation become an integral part of more effort wide For build integrity government . The methods used is descriptive analytical with type study law normative , as well as approach studies library . Data sources include material primary, secondary and tertiary law , processed use analysis qualitative . Research show existence relatedness close between act criminal taxation and corruption , where the weakness accountability law can create gap for practice corruption . With matter the enforcement strict and transparent law required For increase accountability perpetrator act criminal corruption and also irregularities in context taxation that is not seldom each other related . Collaboration between agency government and society are very important in supervise and eradicate practice corruption in the field taxation . In conclusion , strengthening accountability law perpetrator act criminal taxation is step crucial in effort eradication corruption in Indonesia, so that capable create system more taxation fair and effective . Improvement accountability taxation correlated direct with effort eradication more corruption effective .